Smart city development in Taiwan. Issue 3 (2nd April 2021) - Leu, Jang‐Hwa; Lin, Bo‐Chi; Liao, Yen‐Yi; Gan, Dai‐You
Abstract: This article outlines Taiwan's experience in developing smart cities, including visions, implementation strategies and application cases. To take global trends and local needs into account, Taiwan has applied a dual development model that combines top‐down (theme‐based)/bottom‐up (needs‐based) approaches for a synergy effect in balancing innovations and local needs. Furthermore, a public–private partnership program has been adopted to prompt collaboration between central/local authorities with local businesses.Meanwhile, Taiwan uses a private finance initiative program and a global marketing strategy for strengthening the scalability and sustainability of smart city solutions. Three visions in the project help achieve the transformation to ensure smarter urban governance, more comprehensive industrial business models and better livelihoods of residents. Moreover, this article also presents five application cases in the top‐down approach and four application cases in the bottom‐up approach with proven track records which covered eight industry sectors: agriculture, healthcare, education, mobility, retail, energy, governance and environment.